Chapter 31 From ‘pledge’ to ‘public health’ - Mauger, Alice (Taylor & Francis, 2023)
While many nations claim to have a remarkable relationship with drink, perhaps few can rival Ireland for the sustained international attention this impression has received. Combining an historiographical survey of existing works with the author’s own research on medico-scientific and state responses to alcohol addiction, this chapter explores shifting representations of Ireland’s “drinking culture” since the turn of the twentieth century and assesses how competing discourses have influenced attempts to change it. By drawing together these often distinct strands of scholarship, it is intended to present a more rounded picture of the Irish experience than has hitherto existed. Drink in Ireland poses a distinctive case study, given its socio-cultural and political significance at several historical junctures. This chapter traces three distinct phases in which medico-scientific, voluntary and state responses have converged since the 1890s. The first, at the turn of the twentieth century, when medical acceptance of a “disease concept” of inebriety internationally coincided with the establishment of inebriate reformatories, the founding of a new major temperance association and attempts to restrict public house opening hours, all against a backdrop of increased Irish nationalism. The second, in the 1960s, when the re-emergence of medico-scientific interest in alcoholism overlapped with heightened political awareness and activity in the sphere and intersected with attempts to reinvent Ireland’s international profile. The third, in recent years, with Ireland’s adoption of a public health approach to alcohol. The Public Health (Alcohol) Act, 2018 is set to introduce inter alia minimum unit pricing, health warning labels on alcohol products and rigorous restrictions on marketing and advertising. These measures are purportedly aimed at changing Ireland's drinking culture, with politicians and medical experts now framing alcohol as a serious public health problem. While much of this trajectory mirrors the international picture, this chapter argues that Ireland makes for an interesting example of national interests with a long historical lineage, which may provide a useful comparative framework.